2009
DOI: 10.1159/000228726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Centrally Administered Losartan on Gastric and Duodenal Ulcers in Rats

Abstract: The effect of centrally administered losartan, an AT1 receptor antagonist, on gastric acid secretion and gastric cytoprotection was studied using different models of gastric ulcers, such as acetic acid-induced chronic gastric ulcers, pylorus ligation, ethanol-induced and stress-induced acute gastric ulcers and cysteamine hydrochloride-induced duodenal ulcer. Losartan was administered intracerebroventrically (i.c.v.) at 2 different doses (125 and 250 μg/kg). Both doses of losartan increased the heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However, the blockade of AT 1 receptors does not influence gastroprotective action of glucocorticoids released during stress (Filaretova et al, 1998;Pavel et al, 2008). Similarly, AT 1 -receptor antagonists dose-dependently attenuated gastric ulcers in rodents (Merai et al, 2009;Morsy et al, 2009) and counteracted the effects of ischemia and inflammation by the reduction in mucosal neutrophil infiltration and expression of gastric intercellular adhesion molecule 1 and TNF-a (Saavedra et al, 2005(Saavedra et al, , 2006. It is not excluded that the beneficial effect of AT 1 -receptor antagonists could depend on enhancement of the concentration of angiotensin metabolites Ang-(1-7) and Ang-(129) (Neves et al, 2000;Olszanecki et al, 2009), but this hypothesis requires further studies.…”
Section: Discussionmentioning
confidence: 98%
“…However, the blockade of AT 1 receptors does not influence gastroprotective action of glucocorticoids released during stress (Filaretova et al, 1998;Pavel et al, 2008). Similarly, AT 1 -receptor antagonists dose-dependently attenuated gastric ulcers in rodents (Merai et al, 2009;Morsy et al, 2009) and counteracted the effects of ischemia and inflammation by the reduction in mucosal neutrophil infiltration and expression of gastric intercellular adhesion molecule 1 and TNF-a (Saavedra et al, 2005(Saavedra et al, , 2006. It is not excluded that the beneficial effect of AT 1 -receptor antagonists could depend on enhancement of the concentration of angiotensin metabolites Ang-(1-7) and Ang-(129) (Neves et al, 2000;Olszanecki et al, 2009), but this hypothesis requires further studies.…”
Section: Discussionmentioning
confidence: 98%
“…This mucosa protective effect has been proposed to be due to AT1 receptor mediated modulation of inflammatory factors, reduction of sympathetic neural activity and preservation of gastric mucosal blood perfusion (Pavel et al 2008). Reduced gastric acid and increased mucin secretions have been suggested to be other mechanisms of importance for attenuating experimental gastroduodenal ulcerations but the site of interference with the AT1 receptor is then in the CNS (Merai et al 2009). Indomethacin-induced rat small intestinal injuries have been reported to be prevented by the AT1 receptor antagonist CV-11974 .…”
Section: Mucosal Ulcerationsmentioning
confidence: 99%
“…We also indicated the possible inverse association between peptic ulcer and angiotensin type 1 receptor (AT1R) blocker (ARB) or angiotensin I-converting enzyme (ACE) inhibitor, but not any other anti-hypertensive medicine such as Ca-blocker and a or ß-blocker among patients taking low-dose aspirin [6]. The previous experimental animal studies indicated that ARB or ACE inhibitor prevents stress-induced peptic ulcers [7][8][9][10][11][12][13]. However, only our recent clinical study indicated inverse association of ARB or ACE inhibitor with aspirin induced peptic ulcer [6], and clinical data are still lacking.…”
Section: Introductionmentioning
confidence: 99%